Influence of heat treatment in the pyromet 31V turning - Ribeiro, Marcos Valerio [UNESP]; Bahia, Andre Luiz Habib (Springer Nature, 2013)
Considering the constant technological developments in the aeronautical, space, automotive, shipbuilding, nuclear and petrochemical fields, among others, the use of materials with high strength mechanical capabilities at high temperatures has been increasingly used. Among the materials that meet the mechanical strength and corrosion properties at temperatures around 815°C one can find the nickel base alloy Pyromet 31V (SAE HEV8). This alloy is commonly applied in the manufacturing of high power diesel engines exhaust valves where it is required high resistance to sulphide, corrosion and good resistance to creep. However, due to its high mechanical strength and low thermal conductivity its machinability is made difficult, creating major challenges in the analysis of the best combinations among machining parameters and cutting tools to be used. Its low thermal conductivity results in a concentration of heat at high temperatures in the interfaces of workpiece-tool and tool-chip, consequently accelerating the tools wearing and increasing production costs. This work aimed to study the machinability, using the carbide coated and uncoated tools, of the hot-rolled Pyromet 31V alloy with hardness between 41.5 and 42.5 HRC. Through the turning of this alloy we able to analyze the working mechanisms of wear on tools and evaluate the roughness provided on the cutting parameters used. The tests were performed on a CNC lathe machine using the coated carbide tool TNMG 160408-23 Class 1005 (ISO S15) and uncoated tools TNMG 160408-23 Class H13A (ISO S15). Cutting fluid was used so abundantly and cutting speeds were fixed in 75 and 90 m/min. to feed rates that ranged from 0.12, 0.15, 0.18 and 0.21 mm/rev. and cutting depth of 0.8mm. The results of the comparison between uncoated tools and coated ones presented a machined length of just 30% to the first in relation to the performance of the second. The coated tools has obtained its best result for both 75 and 90 m/min. with feed rate of 0.15 mm/rev unlike the uncoated tool which obtained its better results to 0.12 mm/rev.
Keywords: Heat treatment.; Machining; Superalloy